COMPARATIVE STUDY OF E-WALLET ADOPTION IN DEVELOPED AND DEVELOPING COUNTRIES: IMPLICATIONS FOR FINANCIAL INCLUSION - Gunawan Widjaja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to compare the factors that influence the adoption of e-wallets in developed and developing countries and analyse their implications for financial inclusion. The results show that in developing countries, e-wallets play an important role in expanding access to formal finance, especially for the unbanked and micro-entrepreneurs, through ease of access, pro-digital regulations, and mobile technology penetration. Conversely, in developed countries, e-wallet adoption is more focused on improving transaction efficiency and convenience within an already established financial ecosystem, so that its impact on financial inclusion is relatively limited. This study confirms that e-wallet development strategies must be tailored to the social, economic, and regulatory context of each country in order to promote optimal and sustainable financial inclusion.